PERAN KOMITE AUDIT DALAM MEMODERASI PENGARUH VAUSINAS FRAUD HEXAGON TERHADAP PRAKTIK MANAJEMEN LABA PADA PERUSAHAAN KONSTRUKSI DI INDONESIA - Theresia Siwi Kartikawati; Ninik Kurniasih; Endang Kusmana; Arianto, Arianto; Zulham AlFarizi (Bajang Institute, 2025)
This study aims to prove empirically the effect of dividend payments on the quality of the company's earnings and its impact on the predictability of the company's cash flows in the future. The population in this study are companies in the ASEAN region that are included in the ASEAN Asset Class Publicly Listed Companies list. The research method uses the associative method to see the relationship between the existing variables. The results of the study show that companies that pay dividends consistently have better earnings quality than companies that do not pay dividends to their shareholders. Likewise, the effect of firm size on the quality of firm earnings shows that the magnitude of the coefficient of firm size is significant and positive for the two proxies of earnings quality used in this study, namely ADA and AAQ. Thus it can be concluded that the larger the size of the company, the higher the quality of earnings presented by the company. Meanwhile, the test results on other variables show that the company's growth and the company's sales growth do not have a significant effect on the quality of the company's earnings